2,7(3,6)-Diaryl(arylamino)-substituted Carbazoles as Components of OLEDs: A Review of the Last Decade - Gintare Krucaite (MDPI AG, 2021)
Organic light emitting diode (OLED) is a new, promising technology in the field of lighting and display applications due to the advantages offered by its organic electroactive derivatives over inorganic materials. OLEDs have prompted a great deal of investigations within academia as well as in industry because of their potential applications. The electroactive layers of OLEDs can be fabricated from low molecular weight derivatives by vapor deposition or from polymers by spin coating from their solution. Among the low-molar-mass compounds under investigation in this field, carbazole-based materials have been studied at length for their useful chemical and electronic characteristics. The carbazole is an electron-rich heterocyclic compound, whose structure can be easily modified by rather simple reactions in order to obtain 2,7(3,6)-diaryl(arylamino)-substituted carbazoles. The substituted derivatives are widely used for the formation of OLEDs due to their good charge carrier injection and transfer characteristics, electroluminescence, thermally activated delayed fluorescence, improved thermal and morphological stability as well as their thin film forming characteristics. On the other hand, relatively high triplet energies of some substituted carbazole-based compounds make them useful components as host materials even for wide bandgap triplet emitters. The present review focuses on 2,7(3,6)-diaryl(arylamino)-substituted carbazoles, which were described in the last decade and were applied as charge-transporting layers, fluorescent and phosphorescent emitters as well as host materials for OLED devices.